KELARUTAN KALSIUM BATU GINJAL DALAM FRAKSI ETIL ASETAT, N-HEKSANA DAN AIR DARI EKSTRAK ETANOL BUAH TAKOKAK (Solanum torvum Swartz) - Alip Sofiyatun Nisa; Armydha Dwi Susanti (Klinikal Sains : Jurnal Analis Kesehatan, 2023)
Kidney stones are caused by calcium salts in the urine. Takokak fruit (Solanum torvum Swartz) contains chemical compounds of flavonoids, alkaloids, tannins, saponins, quinones and steroids. The content of flavonoids in the takokak plant is thought to be used as a decay of kidney stones. This study aims to determine the levels of dissolved calcium in ethanol extract and several fractions of takokak fruit in vitro. The process of soaking kidney stones was incubated at 37â°C for 5 hours. Dissolved calcium was measured using a Visible spectrophotometer at a Î»max of 506.5 nm. Based on the Ca standard calibration curve, a linear regression equation is obtained y = 0.0162 x + 0.1862 with r2 = 0.9939. In order to obtain the percentage of calcium kidney stones dissolved in the ethanol extract, n-hexane fraction, ethyl acetate fraction and the water fraction of takokak fruit respectively 80.49%; 16.3%; 71.85%, and 33.58%. From these results it can be concluded that the ethanol extract of takokak fruit dissolves calcium kidney stones the most because it is possible that the flavonoid compounds are more interested in the ethanol extract of takokak fruit compared to the ethyl acetate fraction and the water fraction.